Prohibition of genetic discrimination: experience of the USA and Russia - Alimov, Emil V. (Journal of the Belarusian State University. Law, 2021)
The article presents a comparative analysis of the legal regulation of protection against genetic discrimination in the United States and Russia. It is noted that in the United States a number of legislative acts have been adopted on the mentioned topics, active work is being carried out by authorised departments to improve legal regulation in the field of genetic research and the use of their results, as well as in relation to the protection of citizens from genetic discrimination. In the United States, there is no single national act on the protection of citizens from genetic discrimination, which is a feature of this legal system. It is concluded that Russian legislation, as well as law enforcement practice on these issues are fragmented, have many gaps. However, in recent years, a lot of work has been done at the state level in Russia regarding the development of genetic technologies, as well as the creation of the necessary legal framework. It seems that the positive US regulatory experience can be used to improve the legal regulation of the Russian Federation in the field of protecting citizens from genetic discrimination.
Keywords: genetic discrimination; genetic testing; genetic research; human genome; human rights; Russia; USA